Through the Space and Time of Educational Experiences - Holly Sheppard Riesco; Megan Yates Grizzle (University of Oklahoma Libraries, 2022)
This paper applies the Bakhtinian theory of chronotope, literally "time-space," to Jerry Craft's graphic novel New Kid. We examine the definition of chronotope and explore its role in the ELA classroom, as well as its relation to multimodal texts and critical literacies. We argue that an awareness of chronotopic spaces can guide students as they move through the intertextuality of their everyday spaces that shape aspects of their personal and social identities. We begin by outlining our theoretical framework and conclude with an analysis of chronotope, multimodality, and critical literacies in New Kid.